A Methods engineering study of Arms Corporation of the Philippines - Biton, Dennis Paul L.; Cajustin, Jason J.; Lampa, Nelson C.; Liwanag, Kristian E. (Diliman, Quezon City College of Engineering, 1999)
This study seeks to forward recommendation in the study and analysis of an actual industrial setting to improve productivity and layout. It also intends to eliminate unnecessary and non-value-operating operations, such as delays and bottlenecks. The recommendations were made possible through the application of techniques learned from Methods Engineering, like trips matrix, layout planning, etc. The system under study is the production of caliber .45 pistols by Arms Corporation of the Philippines (ARMSCOR). ARMSCOR engages in the manufacture of firearms and ammunition which are in turn sold and distributed to both local and international market. It operates in a 24 hour basis and employs about 450 men out of this, men are directly involved in the shop floor. The main problems addressed are : (1) unfamiliarity with the specifications of the processes. Workers tend to be lax with the specifics of the process operation sheets making them easily get weary of their job and eventually demotivated. (2) Inefficient plant layout. Congestion in the flow of materials results to waste of time and energy on the part of the laborer. (3) Disorganized work area. Working in a disorganized area makes one do things that are not necessarily needed in the operation. The recommendations given are: seminars and training sessions for the workers to aid them in doing the job in the correct way with the least time possible, improve layout with the aid of trips matrix to control/eliminate bottlenecks and delays in the operations, and standardization of work stations especially in the assembly area to permit habit formation for the workers to do their job properly and comfortably, and the installation of jigs and fixtures in the pre-machining and machining areas to lessen task times and improve productivity.
Feasibility study
aSubmitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis